2019
DOI: 10.1093/nar/gkz770
|View full text |Cite
|
Sign up to set email alerts
|

Structural consequences of the interaction of RbgA with a 50S ribosomal subunit assembly intermediate

Abstract: Bacteria harbor a number GTPases that function in the assembly of the ribosome and are essential for growth. RbgA is one of these GTPases and is required for the assembly of the 50S subunit in most bacteria. Homologs of this protein are also implicated in the assembly of the large subunit of the mitochondrial and eukaryotic ribosome. We present here the cryo-electron microscopy structure of RbgA bound to a Bacillus subtilis 50S subunit assembly intermediate (45SRbgA particle) that accumulates in cells upon Rbg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 39 publications
4
69
1
Order By: Relevance
“…S9 ). While some of these GTPases have already been identified in bacteria ( 16 , 17 ) ( SI Appendix , Table S3 ), here they were observed acting together on a maturating ribosomal complex at the reported resolution. GTPases have widespread roles in the cell ( 18 ).…”
Section: Intersubunit Sidementioning
confidence: 50%
“…S9 ). While some of these GTPases have already been identified in bacteria ( 16 , 17 ) ( SI Appendix , Table S3 ), here they were observed acting together on a maturating ribosomal complex at the reported resolution. GTPases have widespread roles in the cell ( 18 ).…”
Section: Intersubunit Sidementioning
confidence: 50%
“…5 c and Extended Fig 9). While some of these GTPase have already been identified in bacteria 15,16 (Extended Data Table 3), this is the first time that they are observed acting together on a maturating ribosomal complex at the reported resolution. GTPases have widespread roles in the cell 17 .…”
Section: Intersubunit Sidementioning
confidence: 62%
“…9 a) interacts with H74-75 of domain V and mt-LAF3 that contacts mt-LAF5 through its N-terminal domain. Similarly to the described roles of these proteins in bacteria, they bind the assembly intermediate rRNA to facilitate the folding of domain IV and V helices 15,16 . The third GTPase, mt-LAF4, is homologous to EngB/YihA in bacteria that was structurally characterized alone, outside the context of the maturing LSU.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies in yeasts reported that deletion of this protein (Mtg1 in yeast) results in respiration deficiency (Barrientos et al 2003). In B. subtilis, where this assembly factor is essential, the LSU:RbgA complex showed that the Nterminal domain overlaps with rRNA H69 and H71, and that the C-terminal helical domain interacts with H62 and H64 (Seffouh et al 2019). In this position, RbgA displaces the P-site and further interacts with the surrounding rRNA, including H92 and H93.…”
Section: Structural Determination and Composition Of The Native Pre-mmentioning
confidence: 99%